Implementasi Manajemen Konflik dalam Mengatasi Pelanggaran Tata Tertib Sekolah - Akbar Karisma; Tri Widayatsih; Syaiful Eddy (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
The purpose seof this study is to analyze how the implementation of conflict management in overcoming violations of school rules at SMP YPI Tunas Bangsa Palembang. This research uses a qualitative approach with a descriptive method. Data sources in this study include primary data collected from principals, teachers, employees, and students of SMP YPI Tunas Bangsa Palembang and secondary data collected from books, theses, theses, documentation of SMP YPI Tunas Bangsa Palembang. Data collection techniques in this study used observation, interviews and documentation. Data validity tests in this study include credibility, dependability, and confirmability tests. While data analysis techniques in this study include transcripts of interview results, data reduction, analysis, data interpretation and triangulation. The result of this study is the implementation of conflict management in overcoming violations of school rules at SMP YPI Tunas Bangsa Palembang consisting of student conflict factors, teacher conflict factors, parent factors, family factors, student character factors, student factors in class, homeroom factors, student home distance factors, school rules factors, problem factors from home and factors related to violations of school rules. In conclusion, the implementation of conflict management in overcoming violations of school rules at YPI Tunas Bangsa Middle School in Palembang consists of conflicts between students and students, students and teachers, teachers and teachers, students and homeroom teachers, parents of students and the school. Keywords: Conflict; Management; Rules of Procedure s; School; Violation